Las autoridades legislativas supremas de un orden jurídico - Redondo, María Cristina (Revus (Ljubljana), 2017)
The first part of this article is about the rules that define a legal order's supreme legislative authority. In this first part, the article also dwells on several distinctions such as those between norms and meta-norms, legislative and customary rules, and constitutive and regulative rules, all with the objective of determining which of these categories the aforementioned rules belong to. The conclusion is that the basic rules defining the supreme legislative authorities of every existing legal order are necessarily constitutive meta-norms and have a customary nature. The second part of this article takes into account the different possible contents of the ultimate rules that define legislative authority. On this basis, four models of legal order and legislative authority are distinguished: those corresponding to absolute authority and to moral authority, and those corresponding to the rule-of-law state and to the constitutional state. In this regard, several considerations are offered that, on the one hand, single out the specific notion of authority accepted within the constitutional state and, on the other, offer a specific critique of the theoretical distinction between constitutive and constituted authority. According to the analysis provided in this article, every authority is a constituted authority. In particular, supreme legislative authorities are constituted by customary constitutive norms that fall beyond the reach of the authorities themselves and do not depend on the decision or will of any particular individual.
Keywords: konstituirana oblast; konstitutivna pravila; pravni red; zakonodajni organi